Instrumen untuk mengukur daya tarik interpersonal pada anak - Bilqis, Fajar (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2018)
The interpersonal attractiveness of children influences social success in the future. However, there are no instruments of interpersonal attraction that are suitable for use in the context of child development, especially in Indonesia. The purpose of the discussion is to formulate an Instrument Attraction Questioner that matches the characteristics of the Indonesian people, especially in the range of children. The research method is a method of developing R&D adaptation from Dick & Carey. The results obtained are a questionnaire consisting of thirty-one items. The questionnaire was tested validated and produced a very strong reliable. The Instrument Attraction Questioner formula helps to evaluate the interpersonal attractiveness of children so that the task of social development can develop properly.